Biostimulant properties of cyanobacterial hydrolysate related to polyamines - Mógor, Átila Francisco; Ördög, Vince; Lima, Guiseppina Pace Pereira [UNESP]; Molnár, Zoltán; Mógor, Gilda (Springer Nature, 2018)
Developing new and natural sources of plant growth promotors is essential to ensure the safe and sustainable production of vegetables for human consumption. In recent years, the potential of microalgae as plant biostimulants has been investigated. Arthrospira platensis (Spirulina platensis) biomass is a recognized protein source and its enzymatic hydrolysis contains molecules such as polyamines with potential to promote plant growth. Therefore, the aim of the present study was to investigate the biostimulant properties of hydrolyzed biomass of A. platensis. Bioassays were performed to determine auxin-like and cytokinin-like bioactivity of the hydrolysates. In addition, its effect on lettuce seedling growth was investigated and an organic system field trail performed where yield and free polyamine levels in leaves quantified. The hydrolysates had a cytokinin-like effect in the bioassay. Foliar applications promoted the growth of lettuce seedlings with the 4-h reaction hydrolysate (Sph4) being the most effective at promoting growth and increasing the spermine content by 64% in the lettuce leaves. The polyamine concentration was also compared in non-hydrolyzed A. platensis and Sph4. Hydrolysis resulted in a 34% increase in spermine content. It was concluded that Sph4 is a natural plant growth promoter that can be used as a raw material for biostimulants, and spermine could be an active compound and a metabolic indicator of Sph4 bioactivity.
Keywords: Arthrospira platensis; Biostimulant; Cyanobacteria; Lactuca sativa; Organic production